Socialist Calculation I:: The Nature and History of the Problem - Hayek, Friedrich August von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this article, the author adresses, under a historical and analytical perspective, the main constitutive elements and the evolution of the discussions regarding the problem of the economic calculation in a socialist community. After a careful conceptual clarification, the author proceeds to present the main Austrian argument that rational economic calculation is possible only in a situation in which the price system, for all economics goods and factors of production, works in an environment of free competition.